Nonparametric econometric methods and applications - Thanasēs Stengos (Journal of Risk and Financial Management, 2019)
An area of very active research in econometrics over the last 30 years has been that of non- and semi-parametric methods. These methods have provided ways to complement more-traditional parametric approaches in terms of robust alternatives, as well as preliminary data analysis. The present Special Issue collects a number of new contributions, both theoretical and empirical that cover a wide spectrum of areas such as financial economics, microeconomics, macroeconomics, labor economics, and economic growth as well as statistical theory and methodology.
Keywords: 330; local smoothing; nonparametric methods; semiparametric methods; wavelets